Parallel Programming Implementation of Williamson Array to Calculate skew-Hadamard Matrices - Yustina Sri Suharini; Melani Indriasari (JURNAL ILMU PENGETAHUAN DAN TEKNOLOGI (IPTEK), 2014)
Research on Hadamard matrices has been doing since 156 years ago and still attracts many researchers around the world. One of the possible reasons is that research in this area has strong relationship with many other areas, so applications related to it are numerous. This is a preliminary research in Hadamard matrices computation, especially in skew-Hadamard calculation. The aim is to implement parallel programming paradigm into several computers so that they can do action together as a parallel computer. To do this research, we used prototyping model process to develop the software, and then we analyzed the calculation result. Our research outcomes are both the prototype software and also the calculation results. Thanks to the Directorate General of Higher Education of Republic Indonesia (DIKTI) who gives us the funding to do this research by PDP scheme 2013.